Sacrococcygeal teratoma: Long‐term outcomes. A UK CCLG Surgeons Group Nationwide Study. Issue 1 (13th October 2022) - Braungart, Sarah; James, Eleanor Ca; Powis, Mark; Gabra, Hany; ,; Losty, Paul D.
Abstract: Aim: Sacrococcygeal teratoma (SCT) is a rare paediatric germ cell tumour (1:40, 000). Long‐term data regarding urinary tract and bowel function after SCT resection is limited to few studies. A UK Children's Cancer and Leukaemia Group (CCLG) Surgeons multicentre study aimed to critically analyse long‐term functional outcomes in patients following resection of SCT. Methods: Nationwide study of UK paediatric surgical oncology centres using a standardised data collection form. All index cases of newborn infants and children <16 years with SCT diagnosis during 2005–2015 were included. Results: 165 SCT patients treated at 14 UK paediatric surgical oncology centres were included. Median age at presentation was 1 day [interquartile range, IQR: 0–25]; median age at surgery was 10 days [IQR: 4–150]. One hundred seventeen (70%) were female and 48 (30%) male. Antenatal diagnosis was made in 44% index cases. Total 59% of patients were Altman Stage I or II lesions. Follow‐up data were available in 83% cases. Tumour recurrence occurred in 13 (7%) patients at median age 13 months [IQR: 8.75–30 months]. Fifty‐nine (36%) of 165 patients had documented adverse bladder or bowel dysfunction. Twenty‐two (37%) cases required urinary clean intermittent catheterisation (CIC) urology health care, with eight patients (14%) needing operative intervention to control management of bowel dysfunction. Conclusion: This UK CCLG study showed 36% of SCT patients develop bladder or bowel dysfunction after primary tumour resection. Functional assessment of bladder and bowel function is mandatory during after‐care follow‐up of all SCT patients. A multidisciplinary care pathway, with surgeon speciality groups including surgical oncology, paediatric urology and paediatric colorectal specialists, is strongly advised to facilitate 'best practice' monitoring of long‐term health and improve patient quality of life (QoL) into adulthood.